Crude Oil Price and Standard of Living Nexus: Evidence from Nigeria - Musa, Kabiru Saidu; Mairiga, Tahir Hussaini; Yakubu, Yahaya (Journal of Developing Economies, 2022)
This article is carried out through an analysis of the influence of crude oil prices on the standard of living in Nigeria by using additional variables as supporters, such as crude oil income, inflation, and exchange rates. According to data availability, the utilization data used in this study is the annual time series data from 1981-2019. The main findings are: (1) there is a long-term equilibrium connection among the series. (2) crude oil price has a negative impact on the standard living. (3) crude oil revenue negatively affects the standard of living. (4) inflation has a negative impact on the standard of living. (5) exchange rate positively affects the standard of living. (6) convergence speed indicates that system movement to the equilibrium path is quick. Therefore, this implies that despite the abundance of oil in the country. The masses do not witness its impact. Diagnostic checks confirmed the perfectness of the model. DOLS, FMOLS and CCR as robustness checks revealed similar results with ARDL long-run results.